KESULITAN DAN SOLUSI PEMBELAJARAN ENGLISH READING TEXT - Dewi Kustanti (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
The activity in teaching learning process is a main activity in education. Whatever that is programmed will be carried in teaching learning process. Teaching learning process will determine its purpose. As an educator or coach, he/she must give attention to individual difference in biology aspect, intellectual and physiological aspect. Those aspects will make close relationship between an educator and a learner. Therefore, in learning English Reading Text, it will be effective if all components in teaching learning process are included. Components in learning are: method, material of learning, tool/ aid of learning, purpose, teacher/ educator, student/ learner. The purpose of reading is an effective reading, but it is at last forgotten by the learner and the student will face many difficult words in reading. To get an effective reading the learner must get main idea from that passage / text. As an educator or coach by digging or understanding student’s difficulties in learning English Reading Text and doing treatment to get their solutions, he/she must make a good program to get good way in teaching reading and the learner will enjoy learning English, especially for Reading.